Growth performance and nutritional concentrations of two kale (Brassica oleracea var Acephala ) varieties in response to fertilizer types in Awka, Southeast Nigeria - Stella Muojiama; Uchenna Nwune; Gladys Ugo; Maryann Ezeh; Uchenna Ukwu (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Soil nutrient depletion is an endemic factor that constitutes one of the greatest limitations to crop production in the tropics. Identifying high yielding kale varieties that thrive best with the most cost-effective fertilizer type can help meet the nutritional deficits of most families in Africa in line with WHO recommendations. The propose of this study was to determine the effect of fertilizer type and variety on growth, calcium (Ca), iron (Fe), and vitamin concentrations of kale.Method: Two kale varieties, curly and lacinato, and three fertilizers, 200 kg ha-1 NPK 20:10:10 (NPK200), 16 t ha-1 poultry manure (PM16), and 100 kg ha-1 NPK 20:10:10 + 8 t ha-1 poultry manure (NPK100+PM8) were evaluated in a 2×3 factorial in randomized complete block design (RCBD) with 3 replications. Data collections were based on selected agronomic, vitamins, and minerals parameters.Results: Fertilizer type, variety and their interaction significantly affected (p<0.05) agronomic traits, minerals, and vitamin contents of kale. PM16 influenced the most significant increases in plant height, leaf number, Ca, Fe, and vitamin-A concentrations whereas, NPK100+PM8 treated plants recorded higher leaf area and weight. Curly variety showed superiority in leaf area, leaf weight, Fe, and vitamin-A whereas, lacinato was higher in plant height, leaf number, Ca, vitamin D and E. Lacinato variety on NPK200 treatment was highest in Ca, vitamin D and E concentrations while curly variety on PM16 was highest in Fe and vitamin A.Conclusion: PM16 and NPK100+PM8 best improved growth, mineral and vitamin concentrations in kale and were therefore recommended for use.